Colonization Sites of USA300 Methicillin-Resistant Staphylococcus aureus in Residents of Extended Care Facilities - Shurland, Simone M. (2009)
BACKGROUND: The anterior nares are the most sensitive single site for detecting methicillin-resistant Staphylococcus aureus (MRSA) colonization. Colonization patterns of USA300 MRSA colonization are unknown. OBJECTIVES: To assess whether residents of extended care facilities who are colonized with USA300 MRSA have different nares or skin colonization findings, compared with residents who are colonized with non-USA300 MRSA strains. METHODS: The study population included residents of 5 extended care units in 3 separate facilities who had a recent history of MRSA colonization. Specimens were obtained weekly for surveillance cultures from the anterior nares, perineum, axilla, and skin breakdown (if present) for 3 weeks. MRSA isolates were categorized as USA300 MRSA or non-USA300 MRSA. RESULTS: Of the 193 residents who tested positive for MRSA, 165 were colonized in the anterior nares, and 119 were colonized on their skin. Eighty-four percent of USA300 MRSA–colonized residents had anterior nares colonization, compared with 86% of residents colonized with non-USA300 MRSA (P=.80). Sixty-six percent of USA300 MRSA–colonized residents were colonized on the skin, compared with 59% of residents colonized with non-USA300 MRSA (P=.30). CONCLUSIONS: Colonization patterns of USA300 MRSA and non-USA300 MRSA are similar in residents of extended care facilities. Anterior nares cultures will detect most—but not all—people who are colonized with MRSA, regardless of whether it is USA300 or non-USA300 MRSA.